Tools to keep communities of practice ticking - Bheenick, Krishan (Technical Centre for Agricultural and Rural Cooperation, 2016)
Krishan Bheenick discusses various online interaction platforms for exchanging information, from email-based platforms and Dgroups to knowledge management blogs.